Diabetes and Hypertension among Patients Receiving Antiretroviral Treatment Since 1998 in Senegal: Prevalence and Associated Factors. (1st December 2012) - Diouf, Assane; Cournil, Amandine; Ba-Fall, Khadidiatou; Ngom-Guèye, Ndèye Fatou; Eymard-Duvernay, Sabrina; Ndiaye, Ibrahima; Batista, Gilbert; Guèye, Papa Mandoumbé; Bâ, Pape Samba; Taverne, Bernard; Delaporte, Eric; Sow, Papa Salif
Abstract : Cardiovascular risk factors in people on antiretroviral treatment (ART) are poorly documented in resource-constrained settings. A cross-sectional study was conducted in 2009 to assess prevalence of diabetes and hypertension in a sample of 242 HIV-infected patients who had initiated ART between 1998 and 2002 in Dakar, Senegal (ANRS 1215 observational cohort). World Health Organization (WHO) criteria were applied to diagnose diabetes and hypertension. Multiple logistic regressions were used to identify factors associated with diabetes and hypertension. Patients had a median age of 46 years and had received ART for a median duration of about 9 years. 14.5% had diabetes and 28.1% had hypertension. Long duration of ART (≥119 months), older age, higher body mass index (BMI), and higher levels of total cholesterol were associated with higher risks of diabetes. Older age, higher BMI at ART initiation, and higher levels of triglycerides were associated with higher risk of hypertension. This study shows that diabetes and hypertension were frequent in these Senegalese HIV patients on ART. It confirms the association between duration of ART and diabetes and highlights the need to implement programs for prevention of cardiovascular risk factors in HIV patients from resource-constrained settings.